An Investigation on the Renal Portal System in Long-Legged Buzzard (Buteo Rufinus) - Selvi̇Ler Si̇Zer, S.; Kabak, M.; Onuk, B. (Chartered Inst. of Building Services Engineers, 2021)
This study was carried out for the morphological examination of renal portal system in the long-legged buzzard. A total of nine adult long-legged buzzards were used in the study. The latex procedure was performed for the macroanatomic detection of the vessels forming the renal portal system. Dissections were performed under the stereomicroscope and later photographs were taken. The renal portal system vessels formed by the cranial renal portal vein and caudal renal portal vein in the long-legged buzzard. Afferent renal branches were separated from these vessels and efferent renal branches were observed to join renal veins. The anastomosis of the left cranial renal portal vein and right cranial renal portal vein was not observed at the cranial side, besides the presence of interiliac anastomosis was determined between the right internal iliac vein and left internal iliac vein at the caudal side. The findings of the renal portal system of long-legged buzzard (Buteo rufinus) were generally similar to those noted in other birds. © 2021, Chartered Inst. of Building Services Engineers. All rights reserved.
Kızıl Şahin’de (Buteo Rufinus) Renal Portal Sistem Üzerine Bir Araştırma
Q4
SCI-Expanded
Keywords: Anatomy; Long-Legged Buzzard; Renal Portal System; Veterinary Sciences